What impact does osteoarthritis have on ability to self-care and receipt of care in older adults? Findings from the Hertfordshire Cohort Study. Issue 4 (December 2022) - Bevilacqua, Gregorio; Laskou, Faidra; Patel, Harnish P.; Westbury, Leo D.; Fuggle, Nicholas R.; Cooper, Cyrus; Dennison, Elaine M.
Abstract: Objectives: Living independently remains the aim of older adults, but musculoskeletal conditions and frailty may hamper this. We examined relationships between osteoarthritis with ability to self-care and access to formal/informal care among community-dwelling older adults, comparing results to relationships between other musculoskeletal conditions of ageing (frailty, sarcopenia, osteoporosis) and these outcomes. Design: Data from the Hertfordshire Cohort Study were used. Osteoarthritis (hand, hip or knee) was defined by clinical examination. Osteoporosis was assessed using dual-energy X-ray absorptiometry and medication use. Sarcopenia was assessed using EWSGOP2 criteria, frailty using Fried criteria. Ability to self-care and access to formal/informal care were self-reported. Results: 443 men and women aged approximately 75 years participated. Osteoarthritis was reported by 26.8% participants; 11.8% had low grip strength; 21.4% had osteoporosis; 8.6% had sarcopenia; 7.6% were identified as frail. Most participants (90.7%) reported no problems with self-care, but more than one-fifth (21.4%) reported having received formal or informal care at home in the previous year. Odds of reporting difficulties with self-care were significantly greater (p ​< ​0.05) for participants with osteoarthritis and for those with frailty, but not for those with osteoporosis or sarcopenia. Odds of receiving care at home in the past year were significantly greater among participants with osteoarthritis and among those with frailty, but not among those with osteoporosis or sarcopenia. Conclusions: Frailty and osteoarthritis were associated with both difficulties with self-care and receipt of care; osteoporosis and sarcopenia were not. These results highlight the contribution of clinical osteoarthritis to ability to live independently in later life, and the need to actively manage the condition in older adults.